The psychological impact of disaster on first responders in the aftermath of Bahanaga train tragedy: A mixed methods approach - Jayaprakash R. Ravan; Udit K. Panda; Jigyansa I. Pattnaik; Sreya Banerjee; Titas Chaudhuri; Sachin Patil; Rama Chandra Das (Indian Journal of Psychiatry)
Background: First responders are at high risk for adverse mental health outcomes following trauma exposure during disaster response. This mixed methods study aimed to quantify psychological impacts and explore personal experiences among first responders after the Bahanaga train accident that killed 294 passengers in the month of June 2023. Methods: For qualitative data, in-depth interviews (IDIs) were conducted, and quantitative data was collected using the PTSD checklist for DSM-5 (PCL-5), generalized anxiety disorder scale (GAD-7), and patient health questionnaire (PHQ-9) for symptoms of post-traumatic stress disorder (PTSD), depression, and anxiety. The study was conducted over one month during July 2023. Results: Among 225 responders, alarming rates of symptoms of probable PTSD (10.2%), anxiety (11.6%), and depression (24.9%) were noted. Those with no prior exposure to disasters and those with no formal training in disaster response scored higher in measures for PTSD. IDIs were conducted with 22 first responders, including various stakeholders. Qualitative analysis identified themes of preoccupation with witnessing trauma, feeling overwhelmed, scary and terrible emotions, avoidance, guilt, hypervigilance, intrusive memories, emotional numbing, unmet needs for mental health support, worsening physical health, re-emergence of past traumas, compounding impact of graphic images in the media, certain positive impact, including increased empathy, resilience and finding purpose, and the beneficial role of peer support. Conclusion: Significant psychological impacts are noted with elevated rates of probable PTSD, anxiety, and depressive symptoms among first responders one month after the Bahanaga train tragedy. These results underscore the vulnerability of first responders to mental health challenges following disaster response in India.